Calculus for computer graphics - Vince, John (London: Springer, 2019)
This book includes applications of calculus in the areas of arc-length parameterisation of curves, geometric continuity, tangent and normal vectors, and curvature.
Introduction -- Functions -- Limits and Derivatives -- Derivatives and Antiderivatives -- Higher Derivatives -- Partial Derivatives -- Integral Calculus -- Area Under a Graph -- Arc Length -- Surface Area -- Volume -- Vector-Valued Functions -- Conclusion
Includes Appendices and Index
Keywords: Calculus; Functions